ANALISIS HAMBATAN EPISTEMOLOGI DIKAJI DARI KEMAMPUAN MENYELESAIKAN MASALAH KONTEKSTUAL BARISAN DAN DERET GEOMETRI - Firmina Eka; Ahmad Yani T; Nurfadilah Siregar; Nadya Febriani Meldi (Universitas Bhinneka PGRI, 2025)
This study aims to identify and analyze students' epistemological obstasles in solving contextual problems of geometric rows and series. The research was based on observations and interviews at Santu Petrus Pontianak Catholic High School which indicated learners' obstacles in solving contextual problems. This study used a qualitative approach with six learners as subjects, who were grouped based on the level of problem solving ability. Data were collected through problem solving ability tests and interviews. Data analysis was conducted using triangulation technique. The results showed that high ability learners did not experience epistemological obstacles. Learners with moderate ability experience obstacles in procedural aspects and operational techniques, such as difficulty choosing formulas and performing calculations. While low ability learners experience obstacles in conceptual, procedural and operational techniques. This research confirms that epistemological obstacles are closely related to problem solving ability. It is hoped that this research will have implications for the development of more effective learning strategies to minimize learners' epistemological obstacles.